Unusual solid-state luminescent push-pull indolones: a general one-pot three-component approach - D'Souza, Daniel M.; Muschelknautz, Christian; Rominger, Frank; Müller, Thomas J. J. (Organic letters, 2010)
In a consecutive three-component cyclocarbopalladation, Sonogashira coupling, Michael addition sequence 4-aminopropenylidene indolones, i.e., terminally fixed push−pull chromophores, are obtained in yields as high as 99%. Most remarkable, however, is the pronounced orange red solid state fluorescence displaying large Stokes shifts of these merocyanines, in particular, since all chromophores are nonfluorescent in solution.
Gesehen am 20.02.2023